Finite Element Analysis of Reinforced Concrete T-Beams with Multiple Web Openings under Impact Loading (Journal of Engineering, 2014)
In this study, a three-dimensional finite element analysis using ANSYS 12.1 program had been employed to simulate simply supported reinforced concrete (RC) T-beams with multiple web circular openings subjected to an impact loading. Three design parameters were considered, including size, location and number of the web openings. Twelve models of simply supported RC T-beams were subjected to one point of transient (impact) loading at mid span. Beams were simulated and analysis results were obtained in terms of mid span deflection-time histories and compared with the results of the solid reference one. The maximum mid span deflection is an important index for evaluating damage levels of the RC beams subjected to impact loading. Three experimental T-beams were considered in this study for calibration of the program. All models had an identical cross-section and span similar to those of the experimental beams. The diameter of the openings of the experimental beams was 110 mm. Three other diameters were varied (50, 80 and 130) mm. The location of the face of the opening with respect to the location of impact loading was investigated (the face of the opening at distance varied 0d, 0.5d, 1d and 1.5d from the location of loading, where d is the effective depth) and the number of web openings was varied (2,4 and 6) openings. All modeled beams subjected to dropping mass of 24.5 kg with height of drop of 250 mm (as for the experimental beams). Results obtained from this study showed that the behavior of beams with circular openings of diameter equal to 22% the web depth has a small effect on the response of the RC T-beams. On the other hand, introducing circular openings with a diameter equal to 35% and 57% of the web depth (80 and 130 mm) increases the maximum mid span deflection by 23% and 43% respectively. Results also showed that, openings with a distance greater than or equal to 1.5 d from the location of impact loading have no effect on the deflection of the RC beams.